Dasometric variables that determine fuel load in oak forests in Guerrero, Mexico - López-López, Bernardo; Aguirre-Calderón, Oscar Alberto; Jiménez-Pérez, Javier; González-Tagle, Marco Aurelio; Alanís-Rodríguez, Eduardo; Méndez-González, Jorge (Ecosistemas y Recursos Agropecuarios, 2024)
Climate change and the lack of fuel management in oak forests promote favorable conditions for the occurrence of forest fires. The objective of the present research was to know the relationship of dasometric variables, terrain slope (Pe), depth of leaf litter (Ph) and depth of mulch (Pm) on the fuel load in oak forests in the Mountain region of Guerrero. The dasometric variables mean diameter (Dm), mean height (Am), number of trees ha-1 (Na) and basal área ha-1 (Ab) were evaluated according to the sampling design of the 2015 National Forest and Soil Inventory; At each sampling site, three planar intersection lines were established for sampling woody material (Ml), leaf litter (Ho) and mulch (Ma) were collected in 0.09 m2. The total fuel load ranged from 23.2 to 46.5 t ha-1 (p < 0.05), the Ma presented the highest load with 43%, followed by woody material (Ml) and leaf litter (Ho) with 31 and 26%. The total charge (Ct) showed a relationship with Ma, Ho and Ml (r = 0.81 to 0.41), Ho with Ph and Pe (r = 0.71 and -0.72). The c1h showed a relationship with Na, Ma, Pe and Dm (r = 0.72 to -0.41), the c10h showed a correlation with Ab, Pe and Na (r = 0.51 to 0.42). The dasometric variables only explain the fuel load with a diameter less than or equal to 2.5 cm.
Keywords: basal area; slope; depth; average diameter; average height